New Genera and Species of Neotropical Amiseginae (Hymenoptera, Chrysididae) - Lynn Siri Kimsey (Psyche: A Journal of Entomology)
The Canadian National Collection (OTTAWA) has one of the largest, if not the largest collection of neotropical Amiseginae in the world. In a sample of about 700 unidentified specimens sent to me by Lubomir Masher from this collection there were many new taxa, including representatives of a new genus. In addition, material was borrowed from the Museum of Comparative Zoology, Harvard University (J. M. Carpenter), Cambridge, Massachusetts, the American Entomological Institute, Gainesville, Florida (H. Townes, GAINESVILLE), and the U.S. National Museum, Washington, D.C. (K. V. Krombein, WASHINGTON). The new species of Adelphe are described separately (Kimsey 1986). The remaining new taxa are included below.